A determinant of islamic banking competitiveness: a study in LFSA / Mohd Fikri Dollah - Dollah, Mohd Fikri (2014)
Islamic bank is similar to the conventional bank by which it performs the same function like lending and others, except that Islamic bank need to operate transaction accordance to the principles of Islam (Henry and Wilson, 2004; Iqbal and Mirakhor, 2007). Shariah which is Islamic law is the guidance for this Islamic Banking which prohibits business that related to sin such as gambling and alcohol. Moreover, riba (interest) and gharar (uncertainty) is also prohibited in this industry (Khan and Khanna, 2010). The main prohibitions on interest banking are because general belief that to earn income without assuming risk is not fair (Siddiqui, 2001). Based on history, Islamic Banking establishes its name due to customer which wants to invest their money in accordance to religious belief (Devlin, 2002). Therefore, it is the objective of Islamic banking that they do not want to be considered as a business entity established not only to satisfy the religious obligations of the Muslim community anymore.